Privatization as a way to tackle the economic recession by diversifying income sources in Iraq - Ahmed Ayad Ibrahem Al-Azzawi, Afeifa Bachai Showket Al-Lami, Iqbal Hashem Mutasher Al-Lami, (Opción, 1970)
The Iraqi economy is a rentier economy that mainly depends on the revenues of crude oil exports, especially after 2003, as a result of the underdevelopment of the infrastructure and vital economic institutions of the country. This also contributed to the aggravation of the economic crisis in it, high unemployment rates, low rates of growth of domestic product and its dependence on fluctuations in international oil prices. For the purpose of achieving economic growth and sectoral interdependence, desires and invitations were generated from international organizations and economists to shift towards a market economy and encourage and urge the private sector to participate in the development of the national economy and address economic recession.